Microsequence heterogeneity and expression of LSU rRNA genes within the two single copy ribosomal transcription units of Theileria parva - Bishop, Richard P.; Gobright, E.I.; Spooner, P.R.; Allsopp, B.A.; Sohanpal, B.K.; Collins, N. (Elsevier, 2000)
The nucleotide sequences of the large subunit ribosomal RNA coding genes within the two single copy ribosomal DNA transcription units of a cloned Theileria parva isolate from a buffalo were determined. The two LSU rRNA coding units differed by 11 nucleotide substitutions and two deletions of 1 and 6 bp, all located in the 5' end of the LSU coding region. We also observed microsequence heterogeneity between the two buffalo parasite LSU sequences and the previously determined LSU rRNA gene of a T. parva parasite isolated from cattle. At all positions which were variable between the two LSU rRNA coding sequences of the buffalo-derived parasite, either unit 1 or unit 2 matched the LSU rRNA coding sequence of the cattle derived T. parva parasite in a mosaic pattern. Synthetic oligonucleotides specific for LSU units 1 and 2 of the buffalo T. parva were developed, and used to assay expression of the two units. Both units were expressed in the intra-lymphocytic schizont stage of T. parva. A. 2-5-10 fold excess of rRNA derived from LSU unit, compared with unit 2 was observed in the schizont stage, the difference being attributable to variation in the level of expression of unit 2. Theileria represents the third genus of Sporozoan protozoa, in addition to Plasmodium and Babesia, exhibiting rRNA coding genes, which are divergent in sequence between different transcription units.